Analisis Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus dan Pengaruhnya Terhadap Alokasi Belanja Modal pada Kabupaten/Kota di Provinsi Jawa Tengah - Puput Nuri Engylia; Darmanto; LMS Kristiyanti (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This study aims to determine the effect of Regional Original Revenue, General Allocation Fund, and Special Allocation Fund on Capital Expenditure Allocation in Regency/City in Central Java Province for the period 2019-2022. The population used in this study were Regencies/Cities in Central Java Province, with a sampling technique, namely purposive sampling, so that the sample taken was 35 districts/cities, consisting of 29 regencies and 6 cities with the period 2019-2022. The type of data used is secondary data, obtained from the APBD Budget and Realization Report on the official website djpk.kemenkeu, and data collection techniques through literature study and documentation. The data analysis method in this study is descriptive statistics and classical assumption tests with hypothesis testing using multiple linier analysis F-test, Determination test, and t-test, Based on the test results, is shows that Regional Original Revenue, and the General Allocation Fund partially have a positive and significant effect on Capital Expenditure. Meanwhile, the Special Allocation Fund partially has no positive and significant effect on Capital Expenditure. Keywords: Regional Original Revenue, General Allocation Funds, Special Allocation Funds, and Capital Expenditure Allocation